2012
DOI: 10.1021/jo300547v
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Arylboron-Based Nucleophiles in Ni-Catalyzed Suzuki–Miyaura Cross-Coupling with Aryl Mesylates and Sulfamates

Abstract: The efficiency of arylboron-based nucleophiles, boronic acid, potassium trifluoroborate, neopentylglycolboronate, and pinacol boronate in nickel-catalyzed Suzuki-Miyaura cross-coupling reactions with the two C-O electrophiles, mesylates, and sulfamates was compared. Arylboronic acid is the most reactive and most atom-economic of the four boron species studied. Arylpotassium trifluoroborate cross-couples efficiently only in the presence of water. In the absence of water, aryl neopentylglycolboronate is more eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 54 publications
1
52
0
1
Order By: Relevance
“…A separate study compared the efficiency of cross-coupling of a neopentylboronic ester with that of a pinacol boronic ester in a nickel catalysed SM coupling reaction. 56 It found, in competition experiments, that more of the neopentyl derivative was consumed than the corresponding pinacol ester, thereby implying its greater reactivity. However, both were found to be less efficient than the corresponding trifluoroborate and boronic acid; the latter being the most reactive overall.…”
Section: Properties and Mechanismmentioning
confidence: 99%
“…A separate study compared the efficiency of cross-coupling of a neopentylboronic ester with that of a pinacol boronic ester in a nickel catalysed SM coupling reaction. 56 It found, in competition experiments, that more of the neopentyl derivative was consumed than the corresponding pinacol ester, thereby implying its greater reactivity. However, both were found to be less efficient than the corresponding trifluoroborate and boronic acid; the latter being the most reactive overall.…”
Section: Properties and Mechanismmentioning
confidence: 99%
“…In 1997, Indolese reported that Ni(II) complexes can be conveniently reduced to the active Ni(0) species at elevated temperature via the homo-coupling of arylboronic acids under basic conditions. [3,[19][20][21][22][23][24][25] Among these Ni catalysts, Ni(COD) 2 and NiCl 2 (PCy 3 ) 2 are the most popularly used catalysts for Suzuki coupling reactions. [3,[19][20][21][22][23][24][25] Among these Ni catalysts, Ni(COD) 2 and NiCl 2 (PCy 3 ) 2 are the most popularly used catalysts for Suzuki coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction has long been the subject of vast research in transition-metal catalysis. Various transition metal complexes [71,72,73,74,75,76,77,78,79] (e.g., Ni, Au, Co, Cu, etc., as such or combined in pairs as heterobimetallic catalysts), or nonconventional Pd(II)-complexes with intricate organic ligands containing S or Se have been intensively explored [80,81]. Efficient transition metal-free catalysts have also been reported for Suzuki–Miyaura cross-coupling reactions [82].…”
Section: Introductionmentioning
confidence: 99%